Development of empirical correlation of peak friction angle with surface roughness of discontinuities using tilt test - Serasa, A.S. (American Institute of Physics Inc., 2016)
The significant influence of surface roughness of discontinuity surfaces is a quantity that is fundamental to the understanding of shear strength of geological discontinuities. This is due to reason that the shear strength of geological discontinuities greatly influenced the mechanical behavior of a rock mass especially in stability evaluation of tunnel, foundation, and natural slopes. In evaluating the stability of these structures, the study of peak friction angle (Î¦peak) of rough discontinuity surfaces has become more prominent seeing that the shear strength is a pivotal factor causing failures. The measurement of peak friction angle however, requires an extensive series of laboratory tests which are both time and cost demanding. With that in mind, this publication presents an approach in the form of an experimentally determined polynomial equation to estimate peak friction angle of limestone discontinuity surfaces by measuring the Joint Roughness Coefficient (JRC) values from tilt tests, and applying the fore mentioned empirical correlation. A total of 1967 tilt tests and JRC measurements were conducted in the laboratory to determine the peak friction angles of rough limestone discontinuity surfaces. A polynomial equation of Ïpeak = -0.0635JRC2 + 3.95JRC + 25.2 that exhibited 0.99 coefficient of determination (R2) were obtained from the correlation of JRC and peak friction angles. The proposed correlation offers a practical method for estimation of peak friction angles of rough discontinuity surfaces of limestone from measurement of JRC in the field. Â© 2016 Author(s).